Spanish educational legislation reforms during the current democratic period: A critical perspective - Vicente Llorent-Bedmar; Verónica Cobano-Delgado Palma (Arizona State University, 2018)
Since the promulgation of the present constitution in 1978, there have been seven important reforms and a plethora of Royal Decrees, Orders, and Regulations, which have meant that changes and modifications are a constant. In Spain, the legal measures adopted unilaterally by the major political parties, conservative and progressive, have lacked the desired consensus, thus impeding their implementation and leading to inconsistent lurches in direction. Following an eminently pragmatic neoliberal ideological perspective, the recent Organic Law on Quality in Education aims to unify the curriculum and give greater autonomy to private centres, with an eye to the labour market. With this reform the democratic participation of the various sectors that make up the educational community is severely curtailed and, in the interests of a higher quality of education, the decision-making powers of the highest participatory body in schools, the School Council, have been reduced to a minimum.